Bacteria Associated to Plants Naturally Selected in a Historical PCB Polluted Soil Show Potential to Sustain Natural Attenuation - Vergani, Lorenzo; Mapelli, Francesca; Marasco, Ramona; Crotti, Elena; Fusi, Marco; Di Guardo, Antonio; Armiraglio, Stefano; Daffonchio, Daniele; Borin, Sara (Frontiers in Microbiology, 2017)
The exploitation of the association between plants and microorganisms is a promising approach able to boost natural attenuation processes for soil clean-up in vast polluted areas characterized by mixed chemical contamination. We aimed to explore the selection of root-associated bacterial communities driven by different plant species spontaneously established in abandoned agricultural soils within a historical polluted site in north Italy. The site is highly contaminated by chlorinated persistent organic pollutants, mainly constituted by polychlorobyphenils (PCBs), together with heavy metals and metalloids, in variable concentrations and uneven distribution. The overall structure of the non-vegetated and root-associated soil fractions bacterial communities was described by high-throughput sequencing of the 16S rRNA gene, and a collection of 165 rhizobacterial isolates able to use biphenyl as unique carbon source was assayed for plant growth promotion (PGP) traits and bioremediation potential. The results showed that the recruitment of specific bacterial communities in the root-associated soil fractions was driven by both soil fractions and plant species, explaining 21% and 18% of the total bacterial microbiome variation, respectively. PCR-based detection in the soil metagenome of bacterial bphA gene, encoding for the biphenyl dioxygenase α subunit, indicated that the soil in the site possesses metabolic traits linked to PCB degradation. Biphenyl-utilizing bacteria isolated from the rhizosphere of the three different plant species showed low phylogenetic diversity and well represented functional traits, in terms of PGP and bioremediation potential. On average, 72% of the strains harbored the bphA gene and/or displayed catechol 2,3-dioxygenase activity, involved in aromatic ring cleavage. PGP traits, including 1-aminocyclopropane-1-carboxylic acid deaminase activity potentially associated to plant stress tolerance induction, were widely distributed among the isolates according to in vitro assays. Plant growth promotion tested in vivo on tomato plants using eleven selected bacterial isolates, confirmed the promotion and protection potential of the rhizosphere bacteria. Different spontaneous plant species naturally selected in a historical chronically polluted site showed to determine the enrichment of peculiar bacterial communities in the soil fractions associated to the roots. All the rhizosphere communities, nevertheless, hosted bacteria with degradation/detoxification and PGP potential, putatively sustaining the natural attenuation process.